APPLICATION OF RICE-STRAW BIOCHAR ALLEVIATES OXIDATIVE STRESS IN WATER-STRESSED Solanum lycopersicum L. - Fawibe, Oluwasegun Olamide; Amidu, Naimot; Chukwurah, Peter Nkachukwu; Akinyemi, Oluwaseun Faith; Ojewumi, Anthony Wale; Gul, Samrin; Dada, Oyeyemi Adigun; Fawibe, Kehinde Oluwaseyi (FUDMA JOURNAL OF SCIENCES, 2025)
Excessive production of reactive oxygen species (ROS) in plant tissues capable of cellular damage has been linked to abiotic stress conditions such as drought. However, the role of biochar as a soil amendment in mitigating the impact of oxidative stress has been under-explored. Therefore, this study investigated the role of biochar in mitigating oxidative stress in Solanum lycopersicum under drought. The pot experiment was designed in a 3 × 4 factorial with five replicates. Factors included biochar application rates: B0 (no biochar), B1 (7.5 gkg-1) and B2 (30 gkg-1); and water regimes: 100% (field capacity, FC), 75% FC, 50% FC and 25% FC. The use of biochar decreased malondialdehyde (MDA) in tomato leaves and roots by 9.3% and 11.8%, respectively, compared with no biochar. On average, B2 decreased MDA and hydrogen peroxide (H2O2) in both leaf and root by 4% and 3.5%, respectively compared with B1. There was a significant interaction between biochar application and water regime in the production of catalase (CAT), ascorbate peroxidase (APx), ascorbic acid (AsA) and glutathione (GSH) in the root of S. lycopersicum. AsA, GSH increased by 51.1% and 27.5%, respectively under 25% FC compared with FC. Biochar decreased ROS by promoting the production of antioxidants (CAT, APx, AsA and GSH), especially under 25%FC. Among biochar levels, B2 was considered optimum for the alleviation of ROS and could be recommended for S. lycopersicum cultivation under drought for stress adaptation. The findings support biochar as a sustainable soil amendment for drought-prone regions.